Characterization of circulating tumor DNA features and exploratory evaluation of the SPOT-MAS assay for non-metastatic colorectal cancer detection - Giang, Pham Truong; Long, Tran Bao; Phuong, Pham Cam; Dung, Tran Ngoc; Truong, Trieu Van; Son, Tran Le; Nghia, Nguyen Hoai; Anh, Luong Thi Lan (Tạp chí Nghiên cứu Y học, 2026)
Colorectal cancer (CRC) is the fifth leading cancer and causes death among all types of cancers in Vietnam. Early detection of colorectal cancer remains challenging, as existing screening methods are either invasive or have limited sensitivity. Circulating tumor DNA (ctDNA) analysis from liquid biopsy offers a promising non-invasive screening methods. Plasma samples from 50 patients with non-metastatic CRC (stages I-III) and 50 healthy controls were analyzed. Multiple cfDNA features, including targeted and genome-wide methylation, copy number alterations (CNAs), and fragment length profiles, were extracted. These cfDNA features were subsequently analyzed using the previously developed SPOT-MAS machine learning model to evaluate the performance of multi-feature ctDNA integration for colorectal cancer detection. CRC samples exhibited widespread genome-wide hypomethylation, targeted hypermethylation of cancer-associated regions (SEPT9), subchromosomal CNAs, and a higher ratio of short cfDNA fragments (≤150 bp) compared with controls. Using integrated multi-feature analysis, SPOT-MAS achieved a sensitivity of 60% and a specificity of 94% for CRC detection. Our results confirm the presence of several known cfDNA features associated with CRC in plasma sample for non-metastatic patients. The preliminary evaluation using the SPOT-MAS framework suggests that integrating multiple cfDNA characteristics may support CRC detection from early stage. However, larger cohorts are required to further validate these finding.